The impact of consultation on length of stay in tertiary care emergency departments. Issue 2 (26th January 2013) - Brick, Craig; Lowes, Justin; Lovstrom, Lindsay; Kokotilo, Andrea; Villa-Roel, Cristina; Lee, Patricia; Lang, Eddy; Rowe, Brian H
Abstract : Background: Consultations in the emergency department (ED) are infrequently studied. This study quantifies the contribution of consultations to ED length of stay (LOS) and examines patient and consultation characteristics associated with prolonged ED LOS. Methods: Prospective cohort study of a convenience sample of shifts by volunteering emergency physicians (EP) at two urban tertiary care Canadian EDs. EPs completed standardised forms on all patients for whom a consultation was requested. Medical chart reviews and secondary analyses of administrative databases were also performed. Factors associated with longer LOS were determined through linear regression modelling. Results: 1180 patients received at least one consultation during study shifts and EPs completed data collection on 841 (71%) of these. Median patient age was 54 years, 53.3% were male, and 2.9% had documented dementia. Admitted patients receiving consultations had a longer overall LOS compared to discharged patients. Median time from triage to consultation request accounted for approximately 28% of the total median LOS in admitted patients compared to 46% for discharged patients. Consultation decision time accounted for 33% and 54% of the LOS for admitted and discharged patients, respectively. Linear regression modelling revealed that advanced age, longer latency between arrival and first consultation request, history of dementia and multiple consultations were significantly associated with longer LOS. Conversely, undergoing procedures while in the ED was associated with a shorter LOS. Conclusions: Consultation decision time contributes significantly to ED LOS. Further efforts are needed to validate these results in other ED settings and improve this aspect of ED throughput.